2016
DOI: 10.1007/s00394-016-1307-9
|View full text |Cite
|
Sign up to set email alerts
|

The amount and types of fatty acids acutely affect insulin, glycemic and gastrointestinal peptide responses but not satiety in metabolic syndrome subjects

Abstract: The amount of fat regardless of the types of fatty acids affects insulin and glycemic responses. Both the amount and types of fatty acids acutely affect the gastrointestinal peptide release in metabolic syndrome subjects, but not satiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…1 of [16]). These results could be in agreement with ours although GLP-1 response was very variable depending on the time period after eating [1516]. …”
supporting
confidence: 92%
See 1 more Smart Citation
“…1 of [16]). These results could be in agreement with ours although GLP-1 response was very variable depending on the time period after eating [1516]. …”
supporting
confidence: 92%
“…Interestingly, GLP-1 response at early phase (30 minutes) after eating was higher after CHO-rich meal compared with fat-rich meal, and SFA meal caused more GLP-1 response than PUFA meal, but opposite results were observed at late phase (6 hours after eating) (Fig. 2A of [ 15 ]). The early phase response of GLP-1 AUC(0–2 hr) was 27% and 23% higher after CHO-rich meal compared with monounsaturated fatty acid (MUFA) and n-6 PUFA meals, respectively (Fig.…”
mentioning
confidence: 99%
“…Several studies have suggested that a high intake of saturated fat naturally present in meat contributes to the risk of glucose intolerance [1,12] due to impaired beta-cell sensitivity and function. Fat quantity and quality have been shown to affect the gastrointestinal peptide release in people with metabolic syndrome [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fat quality, carbohydrate quality needs to be taken into account. The V-meal contained naturally more fiber and less sugar than the M-meal and these differences may have influenced the findings [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dietary intervention based on energy restriction, independently of the distribution of macronutrients, might influence BP and CVD. Accordingly, most scientific evidence highlights the relevance of dietary quality rather than quantity, especially in the management and prevention of MetS [ 8 , 145 , 146 , 147 ]. Moreover, the effectiveness of every dietary intervention is associated with the previous metabolic state (e.g., presence of insulin resistance, T2DM, altered fasting glucose levels, etc.)…”
Section: Other Dietary Patterns and Strategiesmentioning
confidence: 99%